Rice-Fish Impact and Adoption Survey in Southwest and Northern Bangladesh - Ali, Hazrat; Biswas, Ashutosh; Dhar, Palash; Khondker, Murshed-E-Jahan (2025)
The Rice-Fish Impact and Adoption Survey, conducted in Southwest and Northern Bangladesh, aims to provide researchers a comprehensive understanding of farming systems and rice-fish farming practices under the CGIAR initiative on securing the food systems of Asian Mega Deltas for climate and livelihood resilience (AMD). As part of the study, researchers visited 800 households across multiple villages in six districts.